Influence of socio-demographic variables on the choice of contraceptives among women attending ANC unit at specialist hospital Sokoto, Sokoto State, Nigeria - Sabo, Aliyu Sokoto; Yakubu, Lawali; Luba, Aliyu Alkammawa; Ya`u, Samira L.; Bakare, A. T.; Fatima, Muhammad; Zayyanu, Isah M.; Zulkiflu, Musa A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: A contraceptive choice that couples make is a key component of the Sustainable Development Goal agenda and a major contributor to national health. In spite of the importance of increased contraceptive uptake among couples of reproductive ages, meeting the reproductive health rights of women remains an issue due to multi-faceted obstacles within complex environments. The issues which impact women’s reproductive health rights in relation to contraception relate to availability, accessibility, affordability, literacy, tradition, and culture. This study explores the influence of socio-demographic data on the choice of contraceptives among women who are accessing family planning services at a Specialist hospital, Sokoto-Nigeria. Methods: A cross sectional study was used in this quantitative research to generate data on contraceptive choices of women within the reproductive age (18-49 years) who are accessing family planning services at Specialist hospital, Sokoto. A structured questionnaire was used to elicit information from 352 respondents who were randomly sampled at a Specialist hospital, Sokoto-Nigeria. Data was analyzed using SPSS version 20.0. Descriptive statistics, correlation and regression analyses were used in the data analyses. Results: The findings of this study established age, occupation and level of education to be related with the usage and choice of contraceptives among women attending family planning unit at a Specialist hospital in Sokoto. Conclusions: The result of the study indicated that the socio–demographic data of the respondent, has a significant role in the choice of contraceptives among the women attending family planning unit of Specialist Hospital Sokoto.